Literature Review: Dampak Teknologi Digital terhadap Regulasi Emosi Anak Usia Dini dan Peran Pengawasan Orang Tua - Anjani, Ratna (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
This research discusses the impact of digital technology on early childhood emotion regulation and the role of parental supervision. In the digital age, children are increasingly exposed to digital devices, which can affect their mental health and emotional development. The purpose of this study is to identify the relationship between digital technology use and children's mental health, as well as effective parental supervision strategies. The method used was a literature review with a scoping review technique, which allowed mapping the existing literature related to this topic. The findings suggest that unmanaged technology use can increase the risk of emotional and social disorders in children. However, good parental supervision can mitigate these negative impacts. This study contributes to a better understanding of the importance of parents' role in managing technology use among children. The results emphasize the need for family-based interventions to support children's mental health in the digital age.